The Fountainhead - Vidor, King; Cooper, Gary; Neal, Patricia (Burbank, CA : Warner Home Video, 2006)
An uncompromising architect refuses to change his designs and when he discovers the plans for one of his buildings has been changed, he blows up the structure and attempts to defend his actions.
From the novel The fountainhead by Ayn Rand. Originally produced as a motion picture in 1949. Also issued as part of the Gary Cooper the signature collection. Special features: "The making of The fountainhead" documentary featurette; Theatrical trailer.
In English with optional English, French or Spanish subtitles; Closed-captioned. (Container incorrectly states that DVD has French audio track).
film
Keywords: Vidor, King